(untitled) (Central Asian Journal of Medical Sciences, 2021)
Objectives: We have aimed to determine the anti-hypoxic action of antischemin, an active anti-inflammatory drug that protects brain cells from damage and death during cerebral hemorrhage and hypoxia. Methods: We have studied antischemin made from Astragalus membraneceus roots, Scutellaria baicalensis Georgi roots, and Gingko Biloba leaves denizen in Mongolia and compared its protective effect against hypoxia compared to each of its constituents alone 6 groups of 8 mice. Normobaric hypoxia resistance as well as tissue hypoxia resistance was determined. Results: For antischemin preparation 100 mg/kg, the tolerance of normobaric hypoxia was 42 minutes or 47.2% higher in the treatment group (p < 0.001), and the latent period of hypoxia was increased by 22.7% (p < 0.05). The period of hypoxia increased 32% (p < 0.001). Conclusions: Antischemin has been shown to make tissue more resistant to hypoxia and and have more anti-hypoxic activity than its constituents alone.